Traumatic life events and posttraumatic stress disorder among Mexican adolescents: results from a survey Eventos traumáticos de vida y trastorno de estrés postraumático en adolescentes mexicanos: resultados de encuesta - Ricardo Orozco; Guilherme Borges; Corina Benjet; María Elena Medina-Mora; Lizbeth López-Carrillo (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To estimate the prevalence and the association of Traumatic Life Events (LEs) and Posttraumatic Stress Disorder (PTSD) among the Mexico City Metropolitan Area (MCMA) adolescent population. MATERIAL AND METHODS: Adolescents aged 12 to 17 were administered the adolescent version of the World Mental Health Composite International Diagnostic Interview (n=3 005). Data were collected using a stratified, multistage and probability sample. Prevalence, odds ratios and 95% confidence intervals for LEs and PTSD (assessed with DSM-IV criteria) were obtained. RESULTS: The percentage of adolescents reporting at least one traumatic event in their lifetimes was 68.9%, with differences by sex. Prevalence for PTSD were 1.8% (2.4% females and 1.2% males), and sexual-related traumas were the LEs most associated with PTSD [OR=3.9 (CI95%=1.8-8.2)], adjusted by sex, education and age. CONCLUSIONS: Exposure to traumatic life events is not uncommon among Mexico City adolescents. Effort should be made to reduce child and adolescent sexual abuse, a very traumatic event highly associated with PTSD. OBJETIVO: Estimar la prevalencia y la asociación entre los Eventos Traumáticos (ET) y Trastorno de Estrés Postraumático (TEPT) en la población adolescente del Área Metropolitana de la Ciudad de México (AMCM). MATERIAL Y MÉTODOS: 3 005 adolescentes del AMCM entre 12 y 17 años fueron entrevistados empleando la versión para adolescentes de la Entrevista Dia gnóstica Internacional de Salud Mental, en una muestra probabilística, estratificada y multietápica. RESULTADOS: 68.9% de los adolescentes en el AMCM reportaron por lo menos un ET alguna vez en su vida, con diferencias por sexo. La prevalencia de TEPT fue 1.8% (2.4% mujeres y 1.2% hombres), y el abuso sexual se asoció al desarrollo de TEPT [OR=3.9(CI95%=1.8-8.2)], independientemente del sexo, educación o edad. CONCLUSIONES: La exposición a ET es común en los adolescentes. Se debe poner énfasis en los esfuerzos que buscan reducir el abuso sexual en la infancia y la adolescencia, ya que se asocia fuertemente al TEPT.